A "Do‐It‐Yourself" interactive bone structure module: Development and evaluation of an online teaching resource. Issue 2 (1st October 2012) - Rich, Peter; Guy, Richard
Abstract A stand‐alone online teaching module was developed to cover an area of musculoskeletal anatomy (structure of bone) found to be difficult by students. The material presented in the module was not formally presented in any other way, thus providing additional time for other curriculum components, but it was assessed in the final examination. The module was developed using "in‐house" software designed for academics with minimal computer experience. The efficacy and effectiveness of the module was gauged via student surveys, testing student knowledge before and after module introduction, and analysis of final examination results. At least 74% of the class used the module and student responses were positive regarding module usability (navigation, interaction) and utility (learning support). Learning effectiveness was demonstrated by large significant improvements in the post‐presentation test scores for "users" compared with "non‐users" and by the percentage of correct responses to relevant multiple choice questions in the final examination. Performance on relevant short answer questions in the final examination was, on average, comparable to that for other components. Though limited by study structure, it was concluded that the module produced learning outcomes equivalent to those generated by more traditional teaching methods. This "Do‐It‐Yourself" e‐learning approach may be particularly useful for meeting specific course needs not catered for by commercial applications or where there are cost limitations for generation of online learning material. The specific approaches used in the study can assist in development of effective online resources in anatomy. Anat Sci Educ 6: 107–113. © 2012 American Association of Anatomists.